Clinical features, ventilatory management, and outcome of ARDS caused by COVID-19 are similar to other causes of ARDS - Ferrando, Carlos; Suarez-Sipmann, Fernando; Mellado-Artigas, Ricard; Hernández, María; Gea, Alfredo; Arruti, Egoitz; Aldecoa, César; Martínez-Pallí, Graciela; Martínez-González, Miguel A.; Slutsky, Arthur S.; Villar, Jesús (Intensive care medicine, 2020)
Purpose The main characteristics of mechanically ventilated ARDS patients affected with COVID-19, and the adherence to lung-protective ventilation strategies are not well known. We describe characteristics and outcomes of confirmed ARDS in COVID-19 patients managed with invasive mechanical ventilation (MV). Methods This is a multicenter, prospective, observational study in consecutive, mechanically ventilated patients with ARDS (as defined by the Berlin criteria) affected with with COVID-19 (confirmed SARS-CoV-2 infection in nasal or pharyngeal swab specimens), admitted to a network of 36 Spanish and Andorran intensive care units (ICUs) between March 12 and June 1, 2020. We examined the clinical features, ventilatory management, and clinical outcomes of COVID-19 ARDS patients, and compared some results with other relevant studies in non-COVID-19 ARDS patients. Results A total of 742 patients were analysed with complete 28-day outcome data: 128 (17.1%) with mild, 331 (44.6%) with moderate, and 283 (38.1%) with severe ARDS. At baseline, defined as the first day on invasive MV, median (IQR) values were: tidal volume 6.9 (6.3–7.8) ml/kg predicted body weight, positive end-expiratory pressure 12 (11–14) cmH 2 O. Values of respiratory system compliance 35 (27–45) ml/cmH 2 O, plateau pressure 25 (22–29) cmH 2 O, and driving pressure 12 (10–16) cmH 2 O were similar to values from non-COVID-19 ARDS patients observed in other studies. Recruitment maneuvers, prone position and neuromuscular blocking agents were used in 79%, 76% and 72% of patients, respectively. The risk of 28-day mortality was lower in mild ARDS [hazard ratio (RR) 0.56 (95% CI 0.33–0.93), p = 0.026] and moderate ARDS [hazard ratio (RR) 0.69 (95% CI 0.47–0.97), p = 0.035] when compared to severe ARDS. The 28-day mortality was similar to other observational studies in non-COVID-19 ARDS patients. Conclusions In this large series, COVID-19 ARDS patients have features similar to other causes of ARDS, compliance with lung-protective ventilation was high, and the risk of 28-day mortality increased with the degree of ARDS severity.